Influence of Approach Cooperatif Learning Type Jigsaw on the Mathematical Problem-Solving Ability of PGSD Students at STKIP HAMAZAR - Taufik, M.; Jannah, Rauhun (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to describe the influence of the Jigsaw Type Cooperative learning approach, in terms of the problem-solving ability aspect of STKIP Hamzar Semester I Students for the 2024/2025 academic year. This research is a quasi-experimental research with a pre-posttest control group design. This research used two groups, namely the experimental group and the control group. The research population included all Semester I students of the PGSD STKIP Hamzar study program in three classes. From the existing population, two classes I A and Class I) were randomly taken as research samples. Learning basic mathematics concepts in class I A uses a Jigsaw Cooperative learning approach and learning in class I B uses a conventional approach. The instrument of this research is a test of mathematical problem solving abilities. To determine the difference in influence between the Jigsaw Type Cooperative learning approach group and the conventional approach used, an independent sample T-test was carried out to see which variables contributed to the difference. The results of the research show that there is a difference in the influence of the Jigsaw Type Cooperative learning approach and the conventional approach on aspects of the mathematical problem solving abilities of Semester I STKIP Hamzar students.From the research results, it was found that the Jigsaw Type Cooperative learning approach had a more positive effect on the mathematical problem solving abilities of first semester STKIP Hamzar students.